Physiotherapy in patients after ischemic stroke - Aleksandra Ogonowska; Mariola Monika Uczciwek (Kazimierz Wielki University, 2018)
According to the World Health Organisation, ischemic stroke is a clinical syndrome, that is characterized by sudden appearance focal symptoms or global disorders of brain activity. If they do not lead to death earlier, they last over 24 hours and they are caused by vascular reasons. One of the main causes of disability among adults people, both in Poland and in the word, is a recent ischemic stroke . The problem affects usually the men, over 75 years old. Ischemic stroke may appear in different periods of life, although it is disease of an old age. Very often, seven years from first ischemic stroke, the next vascular episode is recorded. Reduction of the risk of disability and improvement of the psychomotor condition of the patient after the recent ischemic stroke is enabled by a quick medical diagnosis and early, long-term rehabilitation, mainly by a physiotherapist.